Establishing a TaqMan-Based Real-Time PCR Assay for the rapid detection and quantification of the newly emerged duck tembusu virus - Yan Liping; Yan Pixi; Zhou Jiewen; Teng Qiaoyang; Li Zejun (Virology Journal, 2011)
Abstract To establish an accurate, rapid, and a quantifiable method for the detection of the newly emerged duck Tembusu virus (DTMUV) that recently caused a widespread infectious disease in ducks in China, we developed a TaqMan-based real-time PCR assay by using E gene-specific primers and a TaqMan probe. This real-time PCR assay was 100 times more sensitive than the conventional PCR. The reproducibility and specificity of the real-time PCR assay were confirmed using plasmids containing E genes or RNAs and DNAs extracted from well-known viruses causing duck diseases. The reliability of this real-time PCR assay was confirmed in 19 of the 24 swab samples, 22 of the 24 tissue samples collected from experimentally infected ducks, as well as 15 of the 21 clinical samples collected from sick ducks since they were verified as DTMUV-positive. The results reveal that the newly established real-time PCR assay might be a useful diagnostic method for epidemiologically investigating and closely observing the newly emerged DTMUV.